Introduction to modern virology - Dimmock, N. J.; Easton, A.J. ;Leppard, K.N. (Hoboken, New Jersey : Wiley Blackwell, 2016)
Praised forits clarity of presentation and accessibility, Introduction to Modern Virology has been a successful student text for over 30 years. It provides a broad introduction to virology, which includes the nature of viruses, the interaction of viruses with their hosts and the consequences of those interactions that lead to the diseases we see. This new edition contains a number of important changes and innovations including: The consideration of immunology now covers two chapters, one on innate immunity and the other on adaptive immunity, reflecting the explosion in knowledge of viral interactions with these systems. The coverage of vaccines and antivirals has been expanded and separated into two new chapters to reflect the importance of these approaches to prevention and treatment. Virus infections in humans are considered in more detail with new chapters on viral hepatitis, influenza, vector-borne diseases, and exotic and emerging viral infections, complementing an updated chapter on HIV. The final section includes three new chapters on the broader aspects of the influence of viruses on our lives, focussing on the economic impact of virus infections, the ways we can use viruses in clinical and other spheres, and the impact that viruses have on the planet and almost every aspect of our lives. A good basic understanding of viruses is important for generalists and specialists alike. The aim of this book is to make such understanding as accessible as possible, allowing students across the biosciences spectrum to improve their knowledge of these fascinating entities.
The nature of viruses -- Virus growth in cells -- Virus interactions with the whole organism -- Viruses and human disease -- Virology : the wider context.
Includes bibliographical references and index.
Keywords: VIROLOGY